2019
DOI: 10.1016/j.clinbiochem.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-26a, miR-106b, miR-107 and miR-133b stratify hepatocellular carcinoma patients according to their response to transarterial chemoembolization

Abstract: Background: A number of hepatocellular carcinoma (HCC) patients have developed resistance against transcatheter arterial chemoembolization (TACE) treatment. In this study, we aimed to develop a panel of microRNAs (miRs) biomarkers to predict clinical outcomes in HCC patients after TACE treatment. Methods: The expression level of twenty miRs was evaluated in FFPE tissues collected from 33 HCC patients. We selected four differentially expressed miRs in TACE-responders versus nonresponders and reassessed their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…In line with our data, it was recently shown that increased serum levels of miR-107 indicate response to TACE treatment [ 18 ]. In this study, several miRNAs were investigated for their potential to predict outcome to TACE treatment.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our data, it was recently shown that increased serum levels of miR-107 indicate response to TACE treatment [ 18 ]. In this study, several miRNAs were investigated for their potential to predict outcome to TACE treatment.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study showed that serum levels of miR-106b, miR-107, and miR-133b were elevated in patients with HCC who responded to TACE, with miR-26a being elevated in nonresponders. miR-26a and miR-133b exhibited the highest diagnostic performance, with miR-133b further distinguishing complete responders from partial responders and non-responders (AUC ≥ 0.90) [151]. Other studies have indicated that a combinatory analysis of plasma levels of miR-21, miR-26a, and miR-29a-3p, or even miR-122 alone, may predict early TACE refractoriness in patients with TACE-treated HCC [152].…”
Section: Cfdnamentioning
confidence: 96%
“…There are almost no reports on the relationship between miR-107 and NSC differentiation, and to date, most studies on miR-107 have been related to cancer. A growing body of evidence indicates that aberrant miR-107 expression plays a key role in cancers, including breast cancer [ 18 ], gastric cancer [ 16 ], cervical cancer [ 36 ], hepatocellular carcinoma [ 2 ], and non-small cell lung cancer [ 35 ]. Prendecki et al indicated that altered miR-107 levels may be a marker of the neurodegenerative process during the course of AD, which is associated with amyloid β metabolism and excessive cell cycle progression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%